1994
DOI: 10.3109/10428199409051659
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prognosis of Centrocytic (Mantle Cell) Lymphoma: A Retrospective Analysis of Twenty-six Patients Treated in One Institution

Abstract: We retrospectively attempted to analyse prognostic factors in a group of 26 patients with centrocytic lymphomas (CCL) treated from 1979 to 1991 (representing 7% of all cases of NHL diagnosed in our institution during that period). Ten of the patients were females and 16 males, and their median age at diagnosis was 69 years (range 38-85). The majority of patients (77%) had advanced disease (Ann Arbor stage III-IV) at presentation. Twenty-two patients (85%) had good performance status (0-1 ECOG). B-symptoms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…4,5 The median survival time is 3 to 5 years and cure is not achieved with current treatment options. 2,[6][7][8][9][10][11] The chromosomal translocation t(11;14)(q13;q32) is characteristic of MCL. This aberration leads to the juxtaposition of the cyclin D1 (CCND1) gene and the immunoglobulin heavy-chain promoter resulting in an overexpression of CCND1.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The median survival time is 3 to 5 years and cure is not achieved with current treatment options. 2,[6][7][8][9][10][11] The chromosomal translocation t(11;14)(q13;q32) is characteristic of MCL. This aberration leads to the juxtaposition of the cyclin D1 (CCND1) gene and the immunoglobulin heavy-chain promoter resulting in an overexpression of CCND1.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of diagnosis of mantle cell lymphoma, peripheral blood involvement may be present-13-21% of cases in most studies (9)(10)(11)(12). The leukemic phase of MCL is defined as an absolute lymphocytic count of greater than 4,000/ microliter; Shivdasani et al reported the leukemic phase to be present in 10-20% of patients with MCL (13).…”
Section: Introductionmentioning
confidence: 99%
“…As the nasopharynx is functionally and developmentally linked to the gastrointestinal tract, it is not surprising that this site is commonly involved as well. Waldeyer's ring is involved at presentation in 20% of patients, but the incidence may be greater with a thorough ear, nose, and throat exam and blind biopsies of nasopharyngeal lymphoid tissue (3). The overlying mucosal epithelium is commonly undisturbed.…”
mentioning
confidence: 99%
“…This pattern of gastrointestinal tract involvement has been referred to as lymphomatous polyposis (2). Twenty percent of patients with MCL present with overt gastrointestinal tract involvement, but with endoscopic evaluation, the incidence increases to 88% (3,4). As the nasopharynx is functionally and developmentally linked to the gastrointestinal tract, it is not surprising that this site is commonly involved as well.…”
mentioning
confidence: 99%